The effects of monensin sodium and Xylanase on corn and wheat based diets - O'Leary, Kirsten; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Due to increase in consumer concern about the use of antibiotics in broiler chick feed, xylanase was tested against monensin sodium to observe if the xylanase had better growth performance in broiler chicks. By comparing the growth performance between the two, it could provide an alternative to the use of monensin sodium in boiler feed products and lessen the concerns of the consumer while decreasing economical cost. The main objective was to compare the growth performance of 216 (6 birds/cage and 6 cages/treatment) one-day old broiler chicks over a twenty-one day period under six diets consisting of: 1) wheat, 2) corn, 3) wheat plus monensin sodium, 4) corn plus monensin sodium, 5) wheat plus xylanase, and 6) corn plus xylanase. Treatments were assigned through random assortment and once a week the body weight and feed intake were recorded to later calculate out BW gain, total feed intake, and FCR of each cage. The data was analyzed using GLIMMIX procedure of SAS with the cages as the experimental units and the treatments as the fixed unit in the study. Based on the results (P<0.01) off of BW gain, total feed intake, FCR, the controlled corn-based diet had improved (P <0.05) FCR in comparison to the control wheat based diet. The wheat-based diets, xylanase (P <0.05) while the Monensin sodium (P >0.05) which improved FCR compared the control wheat diet. The corn-based diet with xylanase nor monensin sodium improved (P >0.05) FCR in comparison to the corn control group. To conclude, although there was minimal impact on antimicrobials in this experiment, the research suggests that xylanase can improve the digestibility of wheat-based diets and restore it to the FCR of that of a corn-based diet.
Keywords: Spring 2017